Solution‐Processable Copolymers Based on Triphenylamine and 3, 4‐Ethylenedioxythiophene: Facile Synthesis and Multielectrochromism. Issue 21 (24th June 2020) - Neo, Wei Teng; Ye, Qun; Chua, Ming Hui; Zhu, Qiang; Xu, Jianwei
Abstract: In comparison with traditional inorganic electrochromic materials, organic polymers offer advantages such as fast switching speed, flexibility, lightweightness, low cost and nontoxicity, solution‐processability, and color tunability. Herein, a series of hyper‐branched copolymers are synthesized from triphenylamine and 3, 4‐ethylenedioxythiophene with different feed ratios via iron(III) chloride (FeCl3 )‐mediated oxidative polymerization. The resultant organic‐soluble polymers are easily processable and their corresponding electrochromic devices are found to be stable with limited degradation upon 2500 cycles. In addition to their facile synthesis to achieve solution‐processable polymers, studies also show that the polymers exhibit multielectrochromic properties and give rise to five colored states upon oxidative‐doping by applying an external voltage between 0 and 2.0 V, providing an interesting example of polymers with unique electrochromic switching among up to five colors, from yellow at the neutral state, to pale green, pale purple, orange, and finally gray. Abstract : A series of hyper‐branched copolymers composed of triphenylamine and 3, 4‐ethylenedioxythiophene are readily synthesized via FeCl3 ‐mediated oxidative polymerization. The polymers exhibit multielectrochromism with five colored states by applying an external voltage between 0 and 2.0 V, and their corresponding electrochromic devices are stable with limited degradation upon 2500 cycles.